Synthesis and biological activity of new salicylanilide N,N-disubstituted carbamates and thiocarbamates - Krátký, Martin; Volková, Marie; Novotná, Eva; Trejtnar, František; Stolaříková, Jiřina; Vinšová, Jarmila (Bioorganic & medicinal chemistry, 2014)
The development of novel antimicrobial drugs represents a cutting edge research topic. In this study, 20 salicylanilide N,N-disubstituted carbamates and thiocarbamates were designed, synthesised and characterised by IR, (1)H NMR and (13)C NMR. The compounds were evaluated in vitro as potential antimicrobial agents against Mycobacterium tuberculosis and nontuberculous mycobacteria (Mycobacterium avium and Mycobacterium kansasii) as well as against eight bacterial and fungal strains. Additionally, we investigated the inhibitory effect of these compounds on mycobacterial isocitrate lyase and cellular toxicity. The minimum inhibitory concentrations (MICs) against mycobacteria were from 4 μM for thiocarbamates and from 16 μM for carbamates. Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus, were inhibited with MICs from 0.49 μM by thiocarbamates, whilst Gram-negative bacteria and most of the fungi did not display any significant susceptibility. All (thio)carbamates mildly inhibited isocitrate lyase (up to 22%) at a concentration of 10 μM. The (thio)carbamoylation of the parent salicylanilides led to considerably decreased cytotoxicity and thus improved the selectivity indices (up to 175). These values indicate that some derivatives are attractive candidates for future research.
Keywords: houby; Methicillin-Resistant Staphylococcus aureus; Salicylanilides; buňky Hep G2; salicylanilidy; antiinfekční látky; Isocitrate lyase inhibition; lidé; Thiocarbamates; Carbamates; thiokarbamáty; Anti-Infective Agents; Microbial Sensitivity Tests; Hep G2 Cells; Fungi; Cytotoxicity; Antimicrobial activity; Salicylanilide carbamate; karbamáty; grampozitivní bakterie; vztahy mezi strukturou a aktivitou; Humans; isocitrátlyasa; viabilita buněk; Cell Survival; methicilin rezistentní Staphylococcus aureus; Gram-Positive Bacteria; Salicylanilide thiocarbamate; Isocitrate Lyase; Mycobacterium avium; mikrobiální testy citlivosti; Structure-Activity Relationship; Antimycobacterial activity; Mycobacterium kansasii